Microwave curing of multidirectional carbon fiber reinforced polymer composites. (15th March 2019) - Li, Yingguang; Li, Nanya; Zhou, Jing; Cheng, Qiang
Abstract: Composite microwave curing technologies have been researched and given great expectations for decades to cutting down the long curing cycle and enormous energy consumption during traditional curing process. However, this good vision was stopped since the microwave can hardly penetrate and heat multidirectional carbon fiber reinforced polymer composites. In this paper, the mechanism that multidirectional composite can hardly be heated was revealed. New method was found to stimulate Vertical Penetrating Microwave (VPM) by using metal strips, and the multidirectional carbon fiber reinforced polymer composites can be heated directly. The theory and model of VPM's heating depth of multidirectional composite were established and verified. The results indicated that 2.3 mm thickness multidirectional composite can be cured effectively by using the VPM.